Rancang Bangun Alat Bantu Penyandang Disabilitas Tangan Untuk Menghidupkan dan Mematikan Perangkat Elektronik Menggunakan Voice Recognition Module V3 - Anas Ardi Firmansyah (Politeknik Negeri Malang, 2016)
In today's modern era, electronic devices have become a necessity that is often used in everyday life. With the development of increasingly advanced science and technology, many things can be used to meet the needs in terms of controlling electronic devices, one of which is controlling electronic devices using voice commands, where this system can be used for people with hand disabilities. In this research, a system will be made using Voice Recognition Module V3 as voice recognition to turn on and turn off electronic devices. The Voice Recognition Module will receive input in the form of voice commands via the microphone as a transducer and is connected to Arduino uno as the main microcontroller which will access the Control Panel which consists of Relay and Contactor components as controlled objects connected to Electronic Devices (Lamps, TV and AC). In the results of the system research, the percentage of successful speech recognition according to the voice sample is 96.6% from 10 times the pronunciation of the command given to each command. While the percentage of success when giving orders only with fragments of words is 21.25%. At the success rate of giving voice commands to different people, the percentage of success is 81%. The success rate for giving commands will be more responsive when in a room without noise or conducive, but the success rate for giving commands will decrease when pronunciation is at a distance of 1M.